Informality as deviancy: the problem of difference in the Decent Work Agenda - Alisson Rowland (Diálogo com a Economia Criativa)
More than half of workers globally are informal workers; operating in non-standard, temporary employment that is often, but not always, poorly paid and unprotected. The Decent Work Agenda (DWA), pioneered by the International Labor Organization (ILO), has been broadly adopted to bridge the concerns of workers and states by pursuing “Decent Work for all”. A core component of the DWA is the reduction of informality. Almost ten years later, however, informality is increasing in many countries. In this paper, I explore the conceptual foundation of the DWA by asking: how does the ILO understand “work” in their 2015 Decent Work Agenda? What are the consequences for those whose rights are protected within global governance projects? I compile a corpus of 36 ILO documents to demonstrate three interlocking discursive schemas: development, paternalism, and colorblindness. While the DWA progressively shifts regulatory discourses, its conceptualization of work constitutes informality as a condition of deviancy. This positions informal workers, who often occupy other vulnerable intersectionalities, as outside the scope of contemporary social protections. Gender, race, class, location and more factor into the formation of global and national labor policies; achieving equitable conditions for all workers requires grappling with the complexity of informality.